Гадаад хэлний сурах бичгийн дасгал даалгаврын шинжилгээний асуудалд: The Analysis of Foreign Language Teaching Textbook Tasks - N., Amarjargal (Mongolian Journal of Foreign Languages and Cultures, 2023)
Due to the development of modern information technology, the structure of foreign language textbooks is becoming more complex. On the other hand, the learning needs of modern learners are wider than they were before. The rationale of this study is the need for a close analysis of textbook exercises and assignments, which are key units in the implementation of language training programs. In the framework of this article, we aim at analyzing the English textbook exercises of General comprehensive school of Mongolia and calculate the results. In order to fulfill the purpose of the research, the objectives include to study the theoretical basis of the analysis of foreign language textbook exercises, carry out a close analysis in “English 3” textbook exercises, and to calculate the results. This model of the close analysis of foreign language textbook exercises which was suggested by Littlejohn in 1998 comprises the following components: 1. Students activities 2. Communication in the classroom 3. Content of exercises and tasks. This model reveals the information about the role of students, classroom communication and curriculum content. Thus, our study has shown that this model of the close analysis of foreign language textbook exercises can be used for selecting appropriate textbooks and for improving the textbook design in teaching practice.